Meningkatkan Kreativitas Siswa Melalui Kegiatan Mewarnai Pola Batik Di SDIT Al-Furqon Palangka Raya - Weny Windasari; Setria Utama Rizal (AMMA : Jurnal Pengabdian Masyarakat, 2024)
This research aims to increase the creativity of grade 2 Al-Ghazali students at SDIT Al-Furqon Palangka Raya through the activity of coloring batik patterns. The methods used in this research were material presentation, practice, discussion and appreciation, with a total of 19 students participating. The research results show that the activity of coloring batik patterns provides space for students to explore colors and patterns, which encourages critical thinking skills and creative problem solving. This activity also introduces local culture and improves students' social skills, such as cooperation and empathy. The research concluded that the activity of coloring batik patterns was effective in developing creativity and fostering appreciation for Indonesian culture in elementary school children.